Aerobic Exercises for Female Prisoners to Reduce Stress Level - Dewi Nurhanifah; Dina Rafidiyah (Comment: an International Journal of Community Development, 2020)
Stress can happen to anyone in life. Stress levels in women are 61% higher than in men. A woman who is forced to live in prison because she is serving a sentence will affect her psychological condition. They will find it difficult to adjust and also have to be separated from their families that impact stress. The solution to this problem is to reduce the level of stress experienced by female prisoners through aerobic exercise. This aerobic exercise was done one time in a week conducted for one month (four meetings) assisted by trained gymnastics instructors. All-female prisoners were measured their stress level before and after a number of aerobic exercises. The stress level experienced by female inmates experienced a 76.2% decline. This is very important because aerobic exercise can improve heart rate and the body's autonomic system which is needed to cope with stress.